Study guides

Q: What is 89 squared?

Write your answer...

Submit

Related questions

It is: 25+64 = 89

a squared plus b squared equals c squared.example: a=5 5sq is 25 b=8 bsq is 64 64+25 or a squared + b squared=89. then you find the square root of 89 and there's your answer. 9.4 [rounded]

13

89

The square root of 7921 is 89.

5 squared = 25 8 squared = 64 64+25=89

The square root of 89 is approximately 9.4 so 9 and 10 are the closest whole numbers. You could also notice that 9 squared is 81 and 10 squared is 100 which are the closest perfect squares to 81.

-- Since you mentioned "hypotenuse", we know you must be talking abouta right triangle.-- Since you're asking for the length of the hypotenuse, we know that the '8'and the '5' must be the lengths of the legs.hypotenuse squared = 8 squared + 5 squaredh squared = 64 + 25h squared= 89h = sqrt(89) = 9.434 (rounded)Angles:-- Since the triangle is a right triangle, one of its angles is 90 degrees,and the other two angles add up to 90 degrees.-- Cosine of one acute angle = 8/sqrt(89). Cosine of the other one = 5/sqrt(89)-- The acute angles are 57.995 degrees and 32.005 degrees. (rounded)square root of 89= 9.434 degrees

This puzzle is also known as Number Puzzle. It is one of Layton's Challenges from The Sweetheart's House. Hint 1: Try treating each digit of a number as a separate entity. Hint 2: Try to find the rule that uses the digits from one number to create the next number in the circle. Hint 3: Try squaring the individual digits first. Solution: That right! It's 89. Square each number and then add these values together to find the next number in the cycle 16 = 4 squared which came from squaring the 2 and the 0 in 20, 1 squared plus 6 squared equals (1x1+6x6)37, 3 squared equals 9 plus 7 squared equals 49 for the number (3x3+7x7)58. 5 squared plus 8 squared equals 25 + 64 equals a total of 89. The number 89 should go in the space.This answer is also correct for Professor Layton and Pandora's Box.

3x squared - x squared = 2x squared

89

9x squared-15x squared = -6

he made the theorem C squared = A squared + B squared and A squared = C squared - B squared or B squared = C squared - A squared

89 in sot-89 = 0

3x squared - (3x) squared = 0

104

9 squared is 81 and 16 squared is 256

100cm squared = 0.01 metres squared

25 squared plus 49 squared is equal to 3,026.

1 cm squared is 10mm by 10mm so 1cm squared equals 100mm squared

3 squared = 9 4 squared = 16 9 x 16 = 144 3 squared x 4 squared = 144

(1 metre) squared = (1000 mm) squared = 1000000 mm squared.

89 * 89 = 7,921

89-0 = 89

13 squared x 4 squared is equal to 2,704.